A comparative study of the radiolysis of used transformer oil and oil containing 1,2,4-trichlorbenzene under the influence of gamma-radiation - Iskenderova, Z.I. (Вопросы атомной науки и техники, 2019)
A comparative study of the radiolysis of used transformer oil and oil containing 1,2,4-trichlorbenzene (TCB) under the influence of gamma-radiation was carried out. Dependence of concentration of H₂, H₂O₂, pH-indicator and IR-spectra of γ-irradiated samples from absorbed doses in the ange of 4…136 kGy was studied. The pH-value dependence and concentration of hydrogen peroxide as a function of the absorbed dose is studied. Irradiation leads to increasing of acidity, related with dechlorination of TCB molecules. It is found that during the radiolysis of transformer oil containing TCB in the presence of dissolved oxygen, radiation-initiated oxidation of the oil takes place (formation of H₂O₂, CO₂). Проведено порівняльне дослідження радіолізу відпрацьованого трансформаторного мастила і мастила, що містить 1,2,4-трихлорбензол, під дією гамма-випромінювання. Вивчено залежність концентрації H₂, H₂O₂, pH-індикатора і ІК-спектрів γ-опромінених зразків від доз у діапазоні 4…136 кГр. Опромінення призводить до підвищення кислотності, пов'язаної з дехлоруванням молекул трихлорбензолу (ТХБ). Вивчено залежність рН-показника і концентрації перекису водню від поглиненої дози. Встановлено, що при радіолізі трансформаторного мастила, що містить ТХБ у присутності розчиненого кисню, відбувається радіаційне окислення мастила (утворення H₂O₂, CO₂). Проведено сравнительное исследование радиолиза отработанного трансформаторного масла и масла, содержащего 1,2,4-трихлорбензол, под воздействием гамма-излучения. Изучена зависимость концентрации H₂, H₂O₂, pH-индикатора и ИК-спектров γ-облученных образцов от доз в диапазоне 4…136 кГр. Облучение приводит к повышению кислотности, связанной с дехлорированием молекул трихлорбензола (ТХБ). Изучена зависимость рН-показателя и концентрации перекиси водорода от поглощенной дозы. Установлено, что при радиолизе трансформаторного масла, содержащего ТХБ в присутствии растворенного кислорода, происходит радиационное окисление масла (образование H₂O₂, CO₂).